Energy Revolution for Our Common Future: An Evaluation of the Emerging International Renewable Energy Law - Karim, Mohammad Ershadul; Munir, Abu Bakar; Karim, Mohammad Ataul; Muhammad Sukki, Firdaus; Abu Bakar, Siti Hawa; Sellami, Nazmi; Bani, Nurul Aini; Hassan, Mohamad Zaki (MDPI, 2018)
Climate change poses profound threats to the Earth and its people. Its mitigation, therefore, demands common but differentiated actions with comprehensive and coordinated approach. The global community has pledged to mitigate various greenhouse gases in some international soft law instruments. Exploitation of renewables to generate energy and produce electricity is simultaneously suggested for the last couple of decades as a viable alternative in mitigating climate change. This gets momentum with the adoption of the historical and universally ratified Paris Agreement in 2016 where energy is placed at the heart of the Agreement. Energy, where renewable energy is a branch, is generally regulated and governed domestically and so, international legal regime is still evolving in this regard. In the absence of any specific and direct international instrument on energy and renewable energy, published literatures have considered this topic from different directions ranging from climate change to the principle of national sovereignty, economic, trade and investment issues. In this backdrop, this paper aims to introduce various renewable sources, prospects and challenges in their promotion that may help to mitigate the adverse effects of climate change. Relevant international law provisions have been evaluated, performances of the relevant regional and international organizations active in this sector are highlighted and some of the disputes in this area considered in international forums are duly addressed. It is revealed that strong political will of the global community in fulfilling their commitments made so far in different international forums is the key to transforming the world into a better one for the future generation.